2004
DOI: 10.1080/14034940310019506
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent and biobanks: a population-based study of attitudes towards tissue donation for genetic research

Abstract: Though genetic research in bioethical debate is often viewed as a potential threat to the integrity of the donor, the confidentiality of medical records still seems to concern donors more. Research ethical committees have support in the majority of the population for some surrogate decisions. The current emphasis on the question of informed consent in policy making for biobank-based research does not seem to be reflected unambiguously in the concerns of the general public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
139
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 5 publications
(4 reference statements)
16
139
3
Order By: Relevance
“…However, some participants also viewed the study-specific model as time-consuming, wasteful, and burdensome, as also observed in prior studies (Hoeyer et al 2004;Master et al 2013;Murphy et al 2009;Platt et al 2013). We found some differences in qualitative themes about the study-specific model by race, with White participants in particular believing that this model would lead to too much contact, while having specific information about secondary research uses and being asked permission for each study were particularly important among Black participants.…”
Section: Time Consuming For Participants and Researcherssupporting
confidence: 62%
See 1 more Smart Citation
“…However, some participants also viewed the study-specific model as time-consuming, wasteful, and burdensome, as also observed in prior studies (Hoeyer et al 2004;Master et al 2013;Murphy et al 2009;Platt et al 2013). We found some differences in qualitative themes about the study-specific model by race, with White participants in particular believing that this model would lead to too much contact, while having specific information about secondary research uses and being asked permission for each study were particularly important among Black participants.…”
Section: Time Consuming For Participants and Researcherssupporting
confidence: 62%
“…Participants who value research may be concerned about the effect of a consent model on the speed of scientific innovation. Simon et al (2011) showed that individuals value types of consent that allow them to provide input and be re-consented in the future, and other researchers have found that this makes participants feel respected (Hoeyer et al 2004;Master et al 2013). Brothers et al (2011) found that participants most preferred an opt-out consent model as opposed to a notice model of consent.…”
Section: Time Consuming For Participants and Researchersmentioning
confidence: 92%
“…They rely on the voluntary participation of the general public, and unwillingness to contribute could compromise the success of some genetic projects. Hypothetical studies, conducted before some of the Biobanks were set up anticipated rates of participation as high as 70%, 4,5 and subsequent findings suggest that the general public are willing to contribute DNA samples to Biobanks despite some concerns about issues such as confidentiality 6 and in the absence of any immediate personal gains. However, formal reports on participation rates are rare.…”
mentioning
confidence: 99%
“…An alternative for 'one-time general consent' is 'one-time specific consent' (providing consent for specific types of future research at one moment) that provides opportunities to have more control over future uses of tissue, but would stifle research (Greely, 1999;Lauri, 2002;Caulfield et al, 2003;Furness and Nicholson, 2004;Dickenson, 2007;Helft et al, 2007) or requires additional resources (Wheeler et al, 2007). Still others argue that informing patients about future research with tissue is impossible, even in basic terms, and that consent cannot be truly 'informed' (Hoeyer et al, 2004).…”
mentioning
confidence: 99%